The Effectiveness of Toddler Massage Implementation on Improving Sleep Quality in Children Aged 1 to 3 years with Sleep Pattern Disturbances in Pengadangan Village: Efektivitas Penerapan Toddler Massage Terhadap Peningkatan Kualitas Tidur pada Anak Usia 1-3 Tahun dengan Gangguan Pola Tidur di Desa Pengadangan - Dina Alfiana Ikhwani; Ismayani (PT. Sentra Ilmiah Teknologi Mandiri, 2026)
Sleep pattern disorders in children aged 1–3 years are common problems that may negatively affect growth, development, cognitive function, and overall well-being. One of the non-pharmacological interventions that can be used to address this problem is toddler massage, which promotes relaxation and is expected to improve sleep quality. This study aimed to determine the effectiveness of toddler massage in improving sleep quality among children aged 1–3 years with sleep pattern disorders in Pengadangan Village. This study employed a descriptive research design using a case study approach. Nursing care was provided over a period of four days. The toddler massage intervention was administered in three sessions, with each session lasting 15 minutes. The findings demonstrated a gradual improvement in sleep quality, as indicated by an increase in nighttime sleep duration from 7 hours to 10 hours, a reduction in the frequency of nighttime awakenings from 5 times to once per night, a decrease in nighttime wakefulness from 2 hours to 10 minutes, and a reduction in sleep onset latency from 45 minutes to 2 minutes. The child's sleep quality improved from the disturbed sleep category to the normal sleep category by the third and fourth days of the intervention. Toddler massage was effective in improving sleep quality among children aged 1–3 years with sleep pattern disorders in Pengadangan Village.